2016
DOI: 10.1108/jd-05-2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

The information behaviours of disadvantaged and disengaged adolescents

Abstract: Purpose: To better understand adolescent information behaviours in disadvantaged and disengaged circumstances, and explore issues of social integration.Design/methodology: Interdisciplinary theoretical framework bringing together theories of information behaviour with theories of social capital. Mixed method design incorporating observation, semi-structured interviews, and focus group conducted in areas of multiple deprivations. ParticipantsÕ young people aged 16-19 not in education, employment or training (NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…Asgari et al (2010) showed that it is indeed long-term interactions with similar others that drive similarity comparisons. Recent research with disadvantaged individuals that use social capital and network theory to predict who people are likely to socialize and interact with shows their networks are predominantly made up of strong ties (Buchanan & Tuckerman, 2016;DiMaggio & Garip, 2012). By observing the behavior of these familiar, close others, individuals learn which outcomes are (un)achievable.…”
Section: Similarity Proxy and Counterfactual Referentsmentioning
confidence: 99%
“…Asgari et al (2010) showed that it is indeed long-term interactions with similar others that drive similarity comparisons. Recent research with disadvantaged individuals that use social capital and network theory to predict who people are likely to socialize and interact with shows their networks are predominantly made up of strong ties (Buchanan & Tuckerman, 2016;DiMaggio & Garip, 2012). By observing the behavior of these familiar, close others, individuals learn which outcomes are (un)achievable.…”
Section: Similarity Proxy and Counterfactual Referentsmentioning
confidence: 99%
“…All felt that they would beneft from IL training, and are only 'somewhat' confident in their own abilities to develop IL skills in their clients. Consequntly, there is limited evidence of transitions to independent information seeking in clients, or underpinning pedagogical practices to achieve such goals, supporting previous findings in similar disadvantaged and dependent circumstances (Buchanan and Tuckerman, 2016;Buchanan et al, 2018). Our findings support previous reports of low IL in nurses (e.g.…”
Section: Discussionmentioning
confidence: 69%
“…Two recent information behaviour studies amongst at-risk populations (Buchanan and Tuckerman, 2016;Buchanan et al, 2018a) have contributed to our understanding of IL in the everyday context, and provided direction for this current work. Buchanan and Tuckerman (2016) in a study of adolescent information behaviours in disadvantaged and disengaged circumstances, worked with UK young people aged 16-19 not in education, employment or training (NEET), and their support workers. NEET youth are an at-risk group as delinquency rates are higher than peers, as is the prevelance of substance abuse and mental health issues (O'Dea et al, 2014;Princes Trust, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Identity as personal project, identity and social groups, and identity as self-presentation were the three most common conceptualizations of identity. Studies that conceptualized identity as personal project focused on how individual's information behaviours (including search and information avoidance) supported and reflected their self-perception and expression (Buchanan & Tuckerman 2016;Meyers 2009). Conceptually, identity as personal project shared much in common with identity as self-presentation; however, while the information behaviours associated with personal identity were largely focused on learning more about, or seeking a reflection of, the self, information behaviours associated with self-presentation were largely focused on using information as a way to display one's identity to others (AL Omar & Cox 2016;Bronstein 2013).…”
Section: Resultsmentioning
confidence: 99%